The effect of caregiver training on time-use of children living in residential care facilities - Koch, Lyndsay Carol (My University, 2011)
Infants and toddlers living in residential care facilities are at risk of developmental delay. Environmental factors contributing to this risk are the temporal context (how children spend their time) and social context (how and when caregivers interact with children). This study compared time-use patterns of children living in residential care facilities where caregiver training had previously taken place versus those in facilities where caregiver training had not taken place using a non-experimental, cross-sectional static group comparison study design. Spot observations were used to estimate time-use patterns of infants and toddlers living in residential care in Johannesburg. Results show that caregiver training increased the quantity of time infants spent with their caregivers (temporal context) and the quality of time toddlers spent with their caregivers (social context). Thus caregiver training has the potential to improve the environment in residential care facilities and can be used as an intervention strategy by occupational therapists.
MSc, Occupational Therapy, Faculty of Health Sciences, University of the Witwatersrand
Keywords: caregiver training; effects; children; residential care facilities